A model and system for an integrated analysis of the iterative life cycle of university-industry partnerships. (2018) - Kaklauskas, A.; Amaratunga, D.; Haigh, R.; Binkyte, A.; Lepkova, N.; Survila, A.; Lill, I.; Tantaee, S.; Banaitis, A.
Abstract: The Asian countries (Sri Lanka, Thailand, Bangladesh) in the ASCENT project have an unequally spread out and restricted RTD ability. An interactive and cooperative university - industry partnership can increase the quality of life and reduce the risk of disaster. Here the fields where universities consider the involvement of industry are recognized (e.g., fundamental and applied research, development, production life cycle and such). There is a recognized need for the private sector to engage the research community in the context of disaster resilience research to tackle disaster risk. The definition of "industry" in this research is deliberately vague to allow exploration of what useful collaborations "industries" can develop with universities for disaster management research (here collaborations mean different life cycle interactions). There is the need for an integrated multiple criteria decision analysis to mitigate the effects of disaster on the built environment at three levels: the micro (research and innovation performance, transfer and absorptive capacity, technology development), meso (institutional arrangements, communication network, local and indigenous rules) and macro (supply and demand, regulations, financing, taxes, culture, traditions, market, climate, political, demographic, technology) levels. Disaster management involves numerous aspects for consideration in addition to making economic, political and legal/regulatory decisions. These must include social, cultural, ethical, psychological, educational, environmental, provisional, technological, technical, organizational and managerial aspects. This research produced a model and a system for integrated analysis of the iterative life cycle of university-industry partnerships. The model and the system make it possible to perform multi-variant design and multiple criteria assessment of alternative university-industry partnership life cycles, calculate their market and investment value, conduct online negotiations, and select options that offer the best efficiency.